1996
DOI: 10.1073/pnas.93.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Identification, sequence, and expression of caveolin-2 defines a caveolin gene family.

Abstract: Caveolin, a 21-to 24-kDa integral membrane protein, is a principal component of caveolae membranes. Caveolin interacts directly with heterotrimeric guanine nucleotide binding proteins (G proteins) and can functionally regulate their activity. Here, an 20-kDa caveolin-related protein, caveolin-2, was identified through microsequencing of adipocyte-derived caveolin-enriched membranes; caveolin was retermed caveolin-1. Caveolins 1 and 2 are similar in most respects. mRNAs for both caveolin-1 and caveolin-2 are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
462
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(478 citation statements)
references
References 31 publications
14
462
1
1
Order By: Relevance
“…Interestingly, among the fragments isolated, a 274 bp fragment resulted similar to mouse caveolin-1 cDNA. Analysis with BLAST program revealed that the PCR fragment isolated was 99% identical over 274 bases to the 3 0 end of the mouse caveolin-1 isoform a mRNA (Figure 1a) (Kogo and Fujimoto, 2000) and 89% identical over 92 bases to the human caveolin-1 mRNA (Glenney, 1992), but was not similar to the mouse or human caveolin-2 or caveolin-3 genes (Scherer et al, 1996;Way and Parton, 1996) (data not shown). PCR product corresponding to caveolin-1 was labeled and used as probe for Northern blot analysis to screen an extended panel of C4HD MPA-treated and untreated tumors from four different animals ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, among the fragments isolated, a 274 bp fragment resulted similar to mouse caveolin-1 cDNA. Analysis with BLAST program revealed that the PCR fragment isolated was 99% identical over 274 bases to the 3 0 end of the mouse caveolin-1 isoform a mRNA (Figure 1a) (Kogo and Fujimoto, 2000) and 89% identical over 92 bases to the human caveolin-1 mRNA (Glenney, 1992), but was not similar to the mouse or human caveolin-2 or caveolin-3 genes (Scherer et al, 1996;Way and Parton, 1996) (data not shown). PCR product corresponding to caveolin-1 was labeled and used as probe for Northern blot analysis to screen an extended panel of C4HD MPA-treated and untreated tumors from four different animals ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Caveolae were first recognized in epithelial cells by electron micrograph techniques over 50 years ago [25]. There are three known caveolin proteins, caveolin 1 (CAV1, with splice variants α and ÎČ), caveolin 2 (CAV2), and caveolin 3 (CAV3) [26][27][28]. CAV1 and CAV2 have overlapping expression patterns in a variety of cell types including, neurons and glia [29,30], endothelial [31], and epithelial cells [32].…”
Section: Caveolins: Important For the Trafficking And Clustering Of Mmentioning
confidence: 99%
“…Recently two homologues of the protein have been identified [29][30][31], with one of these homologues being expressed exclusively in muscle [29,31]. In this review for the sake of simplicity, caveolin-1 will be used instead of VIP21-caveolin (see [41]).…”
Section: Caveolae and Vip21-caveolinmentioning
confidence: 99%